Active manganese adsorption material, preparation method and application
By combining activated carbon with materials such as potassium permanganate, platinum nitrate and cerium nitrate, an efficient catalyst is formed, which solves the problems of low formaldehyde removal efficiency, high cost and environmental protection in the prior art, and achieves efficient removal effect at room temperature.
Patent Information
- Application Number
- CN202311759632.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2024-12-20
- Estimated Expiration
- 2043-12-20
AI Technical Summary
The prior art has problems of low adsorption efficiency, high cost, easy poisoning and poor stability in removing formaldehyde from indoor air, and the traditional catalyst preparation method is complex and not environmentally friendly.
Activated carbon is used as a support, combined with raw materials such as potassium permanganate, platinum nitrate and cerium nitrate, and high-efficiency catalyst is formed through hydrothermal treatment, which uses its high specific surface area and catalytic activity to remove formaldehyde, and works effectively at room temperature.
It achieves efficient, economical and environmentally friendly formaldehyde removal, reduces production costs, and has good stability and durability of the catalyst, which is suitable for large-scale production.
Smart Images

Figure BDA0004618152720000071 
Figure BDA0004618152720000081
Abstract
Description
Technical Field
[0001] The invention relates to the field of air purification, and in particular to an active manganese adsorption material, a preparation method and an application thereof. Background Art
[0002] In the field of air purification, especially for the removal of harmful gases such as formaldehyde in indoor air, the existing technology mainly relies on physical adsorption and chemical catalysis methods. Although these methods are effective to a certain extent, they still have many shortcomings.
[0003] First, although traditional activated carbon adsorption technology performs well in removing volatile organic compounds (VOCs), its adsorption efficiency is not ideal for certain gases, such as formaldehyde. The adsorption capacity of activated carbon is limited by its pore structure and surface functionalization, and its adsorption efficiency is limited for small molecular organic pollutants, especially formaldehyde.
[0004] Secondly, the method based on metal catalysts is effective in the oxidative decomposition of formaldehyde, but there are problems such as high cost, easy poisoning, and poor stability. Precious metal catalysts (such as platinum and palladium) have good catalytic activity at low temperatures, but they are expensive and are easily affected by toxic substances such as sulfides in the air in practical applications, resulting in reduced catalytic efficiency. Although non-precious metal catalysts are lower in cost, they usually require higher temperatures to show good catalytic activity, which limits their application under room temperature conditions.
[0005] In addition, current catalyst preparation methods often involve complex chemical synthesis processes, which not only increase costs but also increase potential environmental impacts. For example, some methods involve high temperature and high pressure reaction conditions, or use toxic chemical reagents, which are not conducive to achieving a green and sustainable production process.
[0006] Under these circumstances, developing an economical and efficient catalyst that can efficiently remove formaldehyde at room temperature while having good stability and durability has become a research focus. The ideal catalyst should combine the high specific surface area and adsorption capacity of activated carbon with the efficient catalytic performance of metal catalysts while avoiding high costs and environmental pollution.
[0007] Therefore, the present invention aims to solve these deficiencies of the prior art and provide a new type of active manganese adsorption material and a preparation method thereof to achieve a more efficient and economical air purification effect. By optimizing the material composition and preparation process, the present invention can not only effectively remove harmful gases such as formaldehyde in indoor air, but also has the advantages of low cost, environmental friendliness, and easy large-scale production. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide an active manganese adsorption material, a preparation method and an application thereof.
[0009] Specifically, the technical solution of the present invention is:
[0010] The invention provides a method for preparing an active manganese adsorption material, comprising the following steps: soaking activated carbon in an aqueous solution containing potassium permanganate, platinum nitrate and cerium nitrate; heating; washing and drying.
[0011] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: soaking activated carbon in an aqueous solution containing potassium permanganate, platinum nitrate and cerium nitrate; heating at 160-200° C. for 6-12 hours; washing and drying.
[0012] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, and 1-3 g / L cerium nitrate at room temperature for 30-90 minutes; then heating at 160-200° C. for 6-12 hours under a nitrogen environment at a pressure of 0.3-0.8 MPa; washing and drying.
[0013] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: soaking activated carbon in an aqueous solution containing potassium permanganate, platinum nitrate, cerium nitrate and an organic acid; heating at 160-200° C. for 6-12 hours; washing and drying.
[0014] Preferably, the organic acid is citric acid and / or tartaric acid.
[0015] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, 1-3 g / L cerium nitrate, and 2-8 g / L organic acid at room temperature for 30-90 minutes; then heating at 160-200° C. for 6-12 hours at a pressure of 0.3-0.8 MPa under a nitrogen environment; washing and drying.
[0016] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: soaking activated carbon in an aqueous solution containing potassium permanganate, platinum nitrate, cerium nitrate, organic acid, and sodium dodecyl sulfate; heating at 160-200° C. for 6-12 hours; washing and drying.
[0017] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, 1-3 g / L cerium nitrate, 2-8 g / L organic acid, and 1-5 g / L sodium dodecyl sulfate at room temperature for 30-90 minutes; then heating at 160-200° C. for 6-12 hours at a pressure of 0.3-0.8 MPa under a nitrogen environment; washing and drying.
[0018] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: soaking activated carbon in an aqueous solution containing potassium permanganate, platinum nitrate, cerium nitrate, organic acid, sodium dodecyl sulfate and urea; heating at 160-200° C. for 6-12 hours; washing and drying.
[0019] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: at room temperature, adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, 1-3 g / L cerium nitrate, 2-8 g / L organic acid, 1-5 g / L sodium dodecyl sulfate, and 3-7 g / L urea, and soaking for 30-90 minutes; then heating at 160-200° C. for 6-12 hours under a nitrogen environment at a pressure of 0.3-0.8 MPa; washing and drying.
[0020] The invention also provides an active manganese adsorption material, which is prepared by the above method.
[0021] The invention also provides an application of an active manganese adsorption material in adsorbing and removing formaldehyde.
[0022] The present invention combines the adsorption capacity of activated carbon's high specific surface area and porous structure with the catalytic efficiency of metal catalysts to construct an efficient and economical catalyst system. The system focuses on improving indoor air quality, especially showing good results in removing formaldehyde pollution commonly found in the environment. DETAILED DESCRIPTION
[0023] A method for preparing an active manganese adsorption material comprises the following steps: adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate and 1-3 g / L cerium nitrate at room temperature for 30-90 minutes; then heating at 160-200° C. for 6-12 hours under a nitrogen environment at a pressure of 0.3-0.8 MPa; and washing and drying.
[0024] The washing step is a conventional washing step, which can be washing with ethanol twice and washing with deionized water twice.
[0025] The drying is a conventional drying step, which may be performed at 80-120° C. for 6-18 hours.
[0026] The method for preparing the active manganese adsorption material of the present invention involves raw materials such as activated carbon, potassium permanganate, platinum nitrate and cerium nitrate, each of which plays a unique role in the preparation process. The following is a detailed analysis of the role of each raw material:
[0027] Activated carbon, as the basic carrier of the present invention, provides a large number of adsorption sites with its high specific surface area and developed porous structure. These characteristics enable activated carbon to effectively capture and adsorb harmful substances in the air, such as formaldehyde. The porous structure on the surface of activated carbon captures pollutant molecules through physical adsorption and provides sufficient surface area for subsequent chemical reactions to occur.
[0028] Potassium permanganate is a strong oxidant, and it may be partially converted into manganese oxide MnO in the reaction. 2 , these manganese oxides can act as effective catalysts to promote the oxidative decomposition of organic pollutants such as formaldehyde. The reaction of potassium permanganate with the surface of activated carbon leads to the deposition of manganese and the formation of catalytically active centers. These centers can catalyze the oxidation reaction and accelerate the decomposition of formaldehyde into harmless substances.
[0029] As a noble metal catalyst, platinum nitrate can improve the catalytic activity of materials, especially the catalytic oxidation of formaldehyde at low temperatures. Platinum nitrate may be reduced in the hydrothermal reaction to form nano-sized platinum particles, which are evenly distributed on the surface of activated carbon, providing additional active sites for the oxidation reaction.
[0030] Cerium nitrate introduces cerium ions, which can further enhance the oxidation capacity of the catalyst by forming cerium oxide. The cerium element in cerium nitrate can promote the activation and transfer of oxygen and accelerate the oxidation and decomposition process of organic pollutants.
[0031] During the entire preparation process, the nitrogen environment provides a non-oxidative reaction condition, avoiding excessive oxidation of the catalyst and maintaining the structure and activity of the material. High temperature and high pressure conditions are conducive to promoting the chemical reaction and ensuring the uniform distribution and effective chemical bonding of the elements in the catalyst. Finally, after washing and drying, the obtained catalyst has excellent catalytic performance and adsorption capacity, and has a significant removal effect on harmful gases such as indoor formaldehyde.
[0032] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, 1-3 g / L cerium nitrate, and 2-8 g / L organic acid at room temperature for 30-90 minutes; then heating at 160-200° C. for 6-12 hours at a pressure of 0.3-0.8 MPa under a nitrogen environment; washing and drying.
[0033] Preferably, the organic acid is citric acid and / or tartaric acid. Both citric acid and tartaric acid are effective organic complexing agents that can form stable complexes with metal ions (such as platinum and cerium ions) in aqueous solutions. This complexing helps to maintain the uniform distribution of metal ions in the solution and avoid local excessive deposition on the surface of activated carbon, thereby improving the uniformity and efficiency of the final catalyst. At the same time, the addition of organic acids citric acid and tartaric acid can affect the pH value of the solution, making it slightly acidic. This acidic environment is conducive to the formation and stability of some metal oxides, especially for the stabilization of the oxidation state of cerium and platinum, which helps to maintain the required chemical environment during the hydrothermal synthesis process. Organic acids may also affect the microstructure and morphology of the catalyst during the hydrothermal synthesis process. In particular, when reacting with metal ions, organic acids may also help form metal oxides of a specific crystal structure, thereby improving the performance of the catalyst. Optimally, the organic acid is composed of 30-70wt% citric acid and 30-70wt% tartaric acid.
[0034] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, 1-3 g / L cerium nitrate, 2-8 g / L organic acid, and 1-5 g / L sodium dodecyl sulfate at room temperature for 30-90 minutes; then heating at 160-200° C. for 6-12 hours at a pressure of 0.3-0.8 MPa under a nitrogen environment; washing and drying.
[0035] In the preparation method of this active manganese adsorbent material, the addition of sodium dodecyl sulfate (SDS) plays several key roles. As a surfactant, SDS can significantly improve the dispersibility of the components in the solution. During the preparation process, it helps metal ions (such as platinum nitrate, cerium nitrate) and other compounds to disperse evenly in water, reduce aggregation and sedimentation, and thus help form a more uniform metal oxide coating on the surface of the activated carbon. SDS also helps stabilize the colloidal particles in the aqueous solution and reduce the sedimentation or agglomeration that may occur during the reaction.
[0036] Preferably, a method for preparing an active manganese adsorption material comprises the following steps: at room temperature, adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, 1-3 g / L cerium nitrate, 2-8 g / L organic acid, 1-5 g / L sodium dodecyl sulfate, and 3-7 g / L urea, and soaking for 30-90 minutes; then heating at 160-200° C. for 6-12 hours under a nitrogen environment at a pressure of 0.3-0.8 MPa; washing and drying.
[0037] In the present invention, urea plays a crucial role as a nitrogen source. During the hydrothermal synthesis process, urea decomposes at high temperature to release ammonia. These ammonia react with the surface of activated carbon to introduce nitrogen doping. The role of nitrogen doping is to change the electronic structure and surface chemical properties of activated carbon. Specifically, the incorporation of nitrogen atoms can introduce additional electron donors or acceptor sites, and these new electronic properties are extremely important for improving the catalytic oxidation ability of activated carbon to pollutants such as formaldehyde. Nitrogen-doped activated carbon exhibits different chemical functionalities on the surface, including increased affinity and catalytic activity for pollutants. One of the direct consequences of nitrogen doping is the improvement of catalytic efficiency. Nitrogen-doped activated carbon can significantly improve the catalytic decomposition ability of organic pollutants such as formaldehyde by changing the surface properties and electronic properties of the material. This improvement is mainly because nitrogen doping changes the electronic environment of the catalyst, thereby providing more active sites for the formaldehyde decomposition process. In addition, the introduction of nitrogen atoms may also improve the catalyst's adsorption and activation ability for oxygen, thereby accelerating the redox reaction. Such changes are crucial for effectively removing organic pollutants such as formaldehyde from the air at room temperature or lower temperatures.
[0038] In the embodiments and comparative examples of the present invention, some raw materials are introduced as follows:
[0039] The activated carbon used is coconut shell activated carbon provided by Mulinsen Activated Carbon Jiangsu Co., Ltd., with a particle size of 10-28 mesh, a filling density of 0.5-0.6 g / mL, and a strength of ≥98%.
[0040] Embodiment 1:
[0041] A method for preparing an active manganese adsorption material comprises the following steps:
[0042] (1) At room temperature, 100 g of activated carbon was added to 1000 mL of an aqueous solution containing 10 g / L potassium permanganate, 2 g / L platinum nitrate, and 2 g / L cerium nitrate for 60 minutes; then heated at 180°C for 9 hours under a nitrogen atmosphere and a pressure of 0.5 MPa;
[0043] (2) Washing: Wash twice with ethanol and then wash twice with deionized water.
[0044] (3) Drying: Dry at 100°C for 12 hours.
[0045] Embodiment 2:
[0046] A method for preparing an active manganese adsorption material comprises the following steps:
[0047] (2) At room temperature, 100 g of activated carbon was added to 1000 mL of an aqueous solution containing 10 g / L potassium permanganate, 2 g / L platinum nitrate, 2 g / L cerium nitrate, and 5 g / L citric acid for 60 minutes; then heated at 180°C for 9 hours under a nitrogen atmosphere and a pressure of 0.5 MPa;
[0048] (2) Washing: Wash twice with ethanol and then wash twice with deionized water.
[0049] (3) Drying: Dry at 100°C for 12 hours.
[0050] Embodiment 3:
[0051] A method for preparing an active manganese adsorption material comprises the following steps:
[0052] (3) At room temperature, 100 g of activated carbon was added to 1000 mL of an aqueous solution containing 10 g / L potassium permanganate, 2 g / L platinum nitrate, 2 g / L cerium nitrate, 5 g / L citric acid, and 3 g / L sodium dodecyl sulfate for 60 minutes; then heated at 180° C. for 9 hours under a nitrogen atmosphere and a pressure of 0.5 MPa;
[0053] (2) Washing: Wash twice with ethanol and then wash twice with deionized water.
[0054] (3) Drying: Dry at 100°C for 12 hours.
[0055] Embodiment 4:
[0056] A method for preparing an active manganese adsorption material comprises the following steps:
[0057] (4) At room temperature, 100 g of activated carbon was added to 1000 mL of an aqueous solution containing 10 g / L potassium permanganate, 2 g / L platinum nitrate, 2 g / L cerium nitrate, 5 g / L citric acid, 3 g / L sodium dodecyl sulfate, and 5 g / L urea for 60 minutes; then heated at 180°C for 9 hours under a nitrogen atmosphere and a pressure of 0.5 MPa;
[0058] (2) Washing: Wash twice with ethanol and then wash twice with deionized water.
[0059] (3) Drying: Dry at 100°C for 12 hours.
[0060] Embodiment 5:
[0061] A method for preparing an active manganese adsorption material comprises the following steps:
[0062] (5) At room temperature, 100 g of activated carbon was added to 1000 mL of an aqueous solution containing 10 g / L potassium permanganate, 2 g / L platinum nitrate, 2 g / L cerium nitrate, 5 g / L tartaric acid, 3 g / L sodium dodecyl sulfate, and 5 g / L urea for 60 minutes; then heated at 180°C for 9 hours under a nitrogen atmosphere and a pressure of 0.5 MPa;
[0063] (2) Washing: Wash twice with ethanol and then wash twice with deionized water.
[0064] (3) Drying: Dry at 100°C for 12 hours.
[0065] Embodiment 6:
[0066] A method for preparing an active manganese adsorption material comprises the following steps:
[0067] (6) At room temperature, 100 g of activated carbon was added to 1000 mL of an aqueous solution containing 10 g / L potassium permanganate, 2 g / L platinum nitrate, 2 g / L cerium nitrate, 2.5 g / L citric acid, 2.5 g / L tartaric acid, 3 g / L sodium dodecyl sulfate, and 5 g / L urea for 60 minutes; then heated at 180°C for 9 hours under a nitrogen atmosphere and a pressure of 0.5 MPa;
[0068] (2) Washing: Wash twice with ethanol and then wash twice with deionized water.
[0069] (3) Drying: Dry at 100°C for 12 hours.
[0070] Comparative Example 1:
[0071] A method for preparing an active manganese adsorption material comprises the following steps:
[0072] (7) At room temperature, 100 g of activated carbon was added to 1000 mL of an aqueous solution containing 10 g / L potassium permanganate and soaked for 60 minutes; then heated at 180°C under a nitrogen atmosphere and a pressure of 0.5 MPa for 9 hours;
[0073] (2) Washing: Wash twice with ethanol and then wash twice with deionized water.
[0074] (3) Drying: Dry at 100°C for 12 hours.
[0075] Comparative Example 2:
[0076] A method for preparing an active manganese adsorption material comprises the following steps:
[0077] (8) At room temperature, 100 g of activated carbon was added to 1000 mL of an aqueous solution containing 10 g / L potassium permanganate, 2 g / L platinum nitrate, 2 g / L cerium nitrate, 5 g / L acetic acid, 3 g / L sodium dodecyl sulfate, and 5 g / L urea for 60 minutes; then heated at 180° C. for 9 hours under a nitrogen atmosphere and a pressure of 0.5 MPa;
[0078] (2) Washing: Wash twice with ethanol and then wash twice with deionized water.
[0079] (3) Drying: Dry at 100°C for 12 hours.
[0080] Test Example 1:
[0081] In a 1-liter sealed cubic container, 0.5 grams of the material of the embodiment or comparative example is evenly spread on the bottom of the closed container. A formaldehyde generator is then used to generate formaldehyde, and the initial formaldehyde concentration in the container is controlled to be 400 mg / L. The temperature is controlled at 20°C, and after being sealed and left to stand for 30 minutes, a formaldehyde detector is used to detect the formaldehyde concentration in the container, and the formaldehyde removal rate (%) is calculated as (concentration before treatment - concentration after treatment) ÷ concentration before treatment × 100.
[0082] Table 1 Formaldehyde removal rate test list
[0083]
[0084]
[0085] The main difference between Example 1 and Comparative Example 1 is the addition of platinum nitrate and cerium nitrate. The introduction of these two additives has a significant effect on improving the formaldehyde removal performance. Platinum in platinum nitrate is a very effective catalyst, especially in oxidation reactions. In the context of formaldehyde removal, platinum can accelerate the oxidative decomposition of formaldehyde. The addition of platinum forms tiny platinum particles on the surface of the activated carbon material, which provide more active sites, thereby improving the ability to catalyze the oxidation of formaldehyde. Cerium in cerium nitrate is a rare earth element with good catalytic properties. The addition of cerium may further enhance the oxidation ability of the material by forming cerium oxide. The introduction of cerium helps to activate and transfer oxygen, thereby accelerating the oxidative decomposition of organic pollutants. In this catalyst system, platinum and cerium may form a synergistic effect. The combination of the efficient catalytic effect of platinum and the oxidative ability of cerium may lead to a significant increase in the overall activity of the catalyst, thereby enhancing the removal efficiency of formaldehyde. By comparing Example 1 and Comparative Example 1, we can see that the addition of platinum nitrate and cerium nitrate significantly improves the formaldehyde removal efficiency. This is not only achieved by increasing the active sites of the catalyst, but also by improving the catalytic activity and stability of the material.
[0086] The main difference between Example 2 and Example 1 is the addition of citric acid, which greatly improves the formaldehyde removal performance. Citric acid, as an effective chelating agent, can form stable complexes with metal ions (such as platinum and cerium ions) in aqueous solution. This complexation helps to evenly disperse the metal ions on the surface or pores of the activated carbon, thereby increasing the active sites and contact area of the catalyst. Through the complexation, citric acid helps to maintain a uniform distribution and a smaller particle size of the metal ions, which is crucial for improving catalytic efficiency and enhancing the adsorption and catalytic decomposition of formaldehyde. The addition of citric acid also affects the pH value of the reaction system, which has an important influence on the catalytic process and the stability of the metal ions. The appropriate pH value helps to improve the stability and activity of the metal catalyst, thereby improving the formaldehyde removal performance.
[0087] The main difference between Example 3 and Example 2 is that the addition of sodium dodecyl sulfate improves the formaldehyde removal performance. As a surfactant, sodium dodecyl sulfate contains both hydrophilic and hydrophobic parts in its molecular structure, which makes it unique in improving the adsorption and catalytic efficiency of materials for formaldehyde. First, sodium dodecyl sulfate interacts with activated carbon through its hydrophobic tail, which can change the surface properties of activated carbon and increase its adsorption capacity for organic pollutants such as formaldehyde. Secondly, the hydrophilic head of sodium dodecyl sulfate helps to form a certain hydrophilic environment on the surface of activated carbon, which may be conducive to the approach and adsorption of formaldehyde molecules. In addition, sodium dodecyl sulfate may also reduce the aggregation of metal catalyst particles in activated carbon and promote a more uniform dispersion of metal ions such as platinum and cerium, thereby improving the activity and stability of the catalyst. This uniform dispersion helps to maximize the contact area of the catalyst and enhance the oxidative decomposition efficiency of formaldehyde.
[0088] The main difference between Example 4 and Example 3 is that the addition of urea improves the formaldehyde removal performance. Urea, as a nitrogen-containing organic compound, plays a key role in enhancing the formaldehyde removal performance when introduced into the activated carbon catalytic system. First, urea may undergo thermal decomposition under high-temperature hydrothermal conditions to generate products such as ammonia and carbodiimide, which can interact with the surface of activated carbon and introduce new functional groups such as amino and carbonyl groups. These newly introduced functional groups not only change the surface properties of activated carbon and enhance its adsorption capacity for formaldehyde, but may also react chemically with formaldehyde to promote its further catalytic decomposition. In addition, the decomposition products of urea may also participate in the dispersion and stabilization process of metal catalysts in activated carbon, helping metal ions such as platinum and cerium to form more uniform and stable catalytic active sites on the surface of carbon materials. This effect helps to improve the activity and durability of the catalyst, thereby enhancing the removal efficiency of the overall material for formaldehyde.
[0089] The main difference between Example 4 and Example 5 and Comparative Example 2 is that the organic acid types used are different, and the performance of citric acid and tartaric acid is significantly better than acetic acid, which is mainly due to the fact that citric acid and tartaric acid, as polyacids, have stronger complexing ability and more complex chemical structure than acetic acid (monoacid). Citric acid and tartaric acid can form more stable and more effective complexes with metal catalysts (such as platinum and cerium) in activated carbon, which not only contributes to the uniform dispersion of metal ions on the surface of activated carbon, but also helps to maintain the active state of metal ions, thereby improving the activity of catalysts and formaldehyde removal efficiency. In addition, polyacids such as citric acid and tartaric acid can also interact more complexly with the activated carbon surface through their multifunctional groups, improving the surface characteristics and adsorption capacity of activated carbon. In contrast, although acetic acid can also act on metal ions, its single acid group and weaker complexing ability limit its effect in catalyst dispersion and activity improvement. Therefore, the application of citric acid and tartaric acid shows a more significant advantage than acetic acid in improving the comprehensive performance and formaldehyde removal efficiency of activated carbon-based catalysts.
[0090] Relative to Examples 4 and 5, the compounding of citric acid and tartaric acid in Example 6 produces a synergistic effect, which is mainly due to the complementary effects of the two organic acids in complexing metal ions and regulating the reaction environment. Citric acid is a polyacid that can form a multi-point coordinated complex with metal ions, effectively stabilize metal ions (such as platinum and cerium) and promote their uniform dispersion on the surface of activated carbon. This dispersion helps to maximize the contact area of the catalyst, thereby enhancing the catalytic oxidation of formaldehyde. Tartaric acid provides different coordination modes, which may play a complementary role in maintaining the stability and activity of metal ions, and may also produce a complementary effect with citric acid in changing the surface chemical properties of activated carbon. In addition, the specific chemical structure of tartaric acid may help to further optimize the pH value of the reaction environment, thereby improving the catalytic efficiency. This compounding of the two not only increases the adsorption capacity of activated carbon to formaldehyde, but also effectively accelerates the decomposition process of formaldehyde by increasing the dispersion and catalytic activity of the metal catalyst. Therefore, the combined use of citric acid and tartaric acid has produced a significant synergistic effect in improving the performance of the catalyst and the efficiency of removing formaldehyde.
Claims
1. A method for preparing an active manganese adsorption material, characterized in that: The method comprises the following steps: adding 100 grams of activated carbon into 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, 1-3 g / L cerium nitrate, 2-8 g / L organic acid and 1-5 g / L sodium dodecyl sulfate at room temperature for 30-90 minutes; then heating at 160-200° C. for 6-12 hours under a nitrogen environment and a pressure of 0.3-0.8 MPa; washing and drying; the organic acid is composed of 30-70 wt% citric acid and 30-70 wt% tartaric acid.
2. The method for preparing the active manganese adsorption material according to claim 1, characterized in that: The method comprises the following steps: adding 100 grams of activated carbon to 500-2000 mL of an aqueous solution containing 6-12 g / L potassium permanganate, 1-3 g / L platinum nitrate, 1-3 g / L cerium nitrate, 2-8 g / L organic acid, 1-5 g / L sodium dodecyl sulfate and 3-7 g / L urea at room temperature for 30-90 minutes; then heating at 160-200° C. for 6-12 hours under a nitrogen environment and a pressure of 0.3-0.8 MPa; washing and drying; the organic acid is composed of 30-70 wt% citric acid and 30-70 wt% tartaric acid.
3. An active manganese adsorption material, characterized in that: The method according to claim 1 or 2 is used for preparation.
4. Use of the active manganese adsorption material as claimed in claim 3 in the adsorption and removal of formaldehyde.
Citation Information
Patent Citations
Nano cerium manganese oxide / activated carbon composite material for oxidation of formaldehyde at room temperature and preparation method thereof
CN107930666A
Supported formaldehyde catalyst and preparation method thereof
CN108126709A
